'Powerlessness' or 'doing the right thing' – Moral distress among nursing home staff caring for residents at the end of life: An interpretive descriptive study. (October 2017) - Young, Amanda; Froggatt, Katherine; Brearley, Sarah G
Background: Caring for dying people can contribute to moral distress experienced by healthcare professionals. Moral distress can occur when this caring is restricted by organisational processes, resources or the provision of futile care. These factors apply to end of life care in nursing homes but research is lacking. Aim: To describe how nursing home staff experience moral distress when caring for residents during and at the end of life. Methods: An interpretive descriptive design, using the critical incident technique in semi-structured interviews to collect data from nursing home staff. Data were analysed using a thematic analysis approach. Setting: Four nursing homes in one large metropolitan area. Participants: A total of 16 staff: 2 nurse managers, 4 nurses and 10 care assistants. Findings: Participants described holding 'good dying' values which influenced their practice. The four practice-orientated themes of advocating, caring, communicating and relating with residents were found to influence interactions with residents, relatives, general practitioners, and colleagues. These led staff to be able to 'do the right thing' or to experience 'powerlessness', which could in turn lead to staff perceiving a 'bad death' for residents. Conclusion: When there are incongruent values concerning care between staff and others involved in the care of residents, staff feel powerless to 'do the right thing' and unable to influence care decisions in order to avoid a 'bad death'. This powerlessness is the nature of their moral distress.